Modelling of noise level in the northern part of Klaipeda city - Vaišis, Vaidotas; Januševičius, Tomas (Journal of Environmental Engineering and Landscape Management, 2009)
Noise is an urgent problem not only in Lithuania but also all over the world. There are no noise‐reducing walls in the northern part of Klaipeda that could be used as reducers of noise spread from streets to the residential territory. Equivalent noise level spread from streets to the residential territory during the day and night time is modelled in this work. Comparison of measured and modelled noise level is carried out. A wall made from plastics, wood and ferroconcrete was used as a noise reducer in a model for reducing noise level spread to the residential territory. A wall of 2 and 3 m height was also used for wall efficiency study. Noise level dependence on car velocity is determined in I. Kantas street which is cobbled with stones. Modelling of noise level dependence on car velocity in I. Kantas street is also carried out and modelling results are compared with experimental results.Triukšmo lygio šiaurinėje Klaipėdos dalyje modeliavimasSantrauka. Triukšmas – ne tik Lietuvoje, bet ir visame pasaulyje aktuali problema. Šiaurinėje Klaipėdos dalyje nėra triukšmą mažinančių sienelių, kurios slopintų triukšmo sklidimą nuo gatvių į gyvenamąją teritoriją. Sumodeliuotas ekvivalentinis triukšmo, sklindančio nuo gatvių į gyvenamąją teritoriją dieną ir naktį, lygis. Išmatuotasis ir sumodeliuotas triukšmo lygiai palyginami. Sumodeliuotas triukšmo lygio gyvenamojoje teritorijoje sumažėjimas esant plastikinei, medinei ir gelžbetoninei sienelei nuo triukšmo. Atlikta 2 ir 3 m aukščio sienelių efektyvumo tyrimas bei triukšmo lygio priklausomumo nuo automobilių greičio akmenimis grįstoje I. Kanto gatvėje analizė. Palyginti triukšmo lygio dėl automobilių greičio I. Kanto gatvėje modeliavimo ir matavimo rezultatai.Reikšminiai žodžiai: triukšmo lygis, triukšmą mažinančių sienelių efektyvumas, gyvenamoji teritorija.Моделирование шумового уровня в северной части города KлайпедыРезюме. Проблема шума является актуальной не только в Литве, но и во всем мире. В северной части города Клайпеды нет заградительных стенок, которые уменьшали бы распространение уличного шума в жилые зоны. Построена модель распространения уровня эквивалентного шума с улиц в жилые зоны днем и ночью, проведен сравнительный анализ измеренного и смоделированного шума. Построена модель уменьшения уровня шума при наличии стенок из пластика, дерева, железобетона. Проведены исследования эффективности стенок по уменьшению распространения шума при их высоте в 2 и 3 м. Проведены исследования зависимости уровня шума от скорости движения автомобилей по булыжной мостовой ул. И. Канта, построена модель. Проведен сравнительный анализ уровня измеренного и смоделированного шума для ул. И. Канта.Ключевые слова: уровень шума, эффективность стенок по уменьшению распространения шума, жилая зона.First Published Online: 14 Oct 2010